Dimerization of human immunodeficiency virus type 1 RNA involves sequences located upstream of the splice donor site. - Marquet, R (1994)
The retroviral genome consists of two homologous RNA molecules associated close to their 5' ends. We studied the spontaneous dimerization of four HIV-1 RNA fragments (RNAs 1-707, 1-615, 311-612, and 311-415) containing the previously defined dimerization domain, and a RNA fragment (RNA 1-311) corresponding to the upstream sequences. Significant dimerization of all RNAs is observed on agarose gels when magnesium is included in the electrophoresis buffer. In contrast to dimerization of RNAs 311-612 and 311-415, dimerization of RNAs 1-707, 1-615 and 1-311 strongly depends on the size of the monovalent cation present in the incubation buffer. Also, dimerization of RNAs 1-707, 1-615, and 1-311 is 10 times faster than that of RNAs 311-612 and 311-415. The dimers formed by the latter RNAs are substantially more stable than that of RNA 1-615, while RNA 1-311 dimer is 5-7 degrees C less stable than RNA 1-615 dimer. These results indicate that dimerization of HIV-1 genomic RNA involves elements located upstream of the splice donor site (position 305), i.e. outside of the previously defined dimerization domain.